PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP RETURN SAHAM (Studi pada Perusahaan Sub Sektor Property dan Real Estate yang Tercatat di Bursa Efek Indonesia Tahun 2016-2019) - latifah, syarifah (Journal of Fundamental Management (JFM), 2022)
This study aims to determine the Effect of Profitability, Liquidity and Leverage on Stock Returns in Property and Real Estate Sub-Sector Companies listed on the IDX (Indonesian Stock Exchange) in 2016-2019. The population in this study is the property and real estate sub-sector listed on the Indonesia Stock Exchange (IDX) in 2016-2019 with a total research sample of 18 companies determined by purposive sampling method and there are 72 data processed in the study. The test method uses the coefficient of determination, t-statistical test, and F statistical test. The data analysis used is panel data regression analysis with Eviews 9 software tools. The results of this study indicate that the partial liquidity test has an effect on stock returns. However, profitability and leverage have no effect on stock returns.